2006
DOI: 10.1182/blood-2006-03-008946
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of suppressors of cytokine signaling in toll-like receptor–mediated block of dendritic cell differentiation

Abstract: IntroductionInnate immunity represents the first line of defense against invading pathogens. Tissue-resident immune cells, including macrophages and dendritic cells (DCs), are the first immune cells to encounter infectious agents. Recognition of infecting pathogens within these cells is performed by now well-known pattern recognition receptors responding to conserved microbial structures. 1 Among these receptors, toll-like receptors (TLRs) have been identified as playing a pivotal role and indeed, both macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 34 publications
4
63
2
Order By: Relevance
“…When isolated CD14 1 monocytes were stimulated with in the presence of LPS, cells failed to upregulate the DC marker CD1a and retained CD14 expression [5], which contrasts the phenotype obtained with G4 stimulation alone. When we tested other TLR agonists, we found that the TLR7/8 small molecular weight agonist R848 influences the differentiation of DCs in a comparable manner (Fig.…”
Section: Phenotype Of Tlr-apcsmentioning
confidence: 78%
See 2 more Smart Citations
“…When isolated CD14 1 monocytes were stimulated with in the presence of LPS, cells failed to upregulate the DC marker CD1a and retained CD14 expression [5], which contrasts the phenotype obtained with G4 stimulation alone. When we tested other TLR agonists, we found that the TLR7/8 small molecular weight agonist R848 influences the differentiation of DCs in a comparable manner (Fig.…”
Section: Phenotype Of Tlr-apcsmentioning
confidence: 78%
“…The effect on CD11c could be traced back to a SOCS-1 dependent blockade of STAT-5 phosphorylation. Additionally, we could show that SOCS-3 is also able to reduce STAT-5 phosphorylation [5]. Since TLR-APC upregulate preferentially SOCS3 (data not shown) we suppose that in the human system the block of STAT-5 might be SOCS-3-dependent.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…GM-CSF is an essential factor in the generation of DCs. Although signaling through TLRs induced the maturation of DCs from iDCs, it suppressed GM-CSF-mediated DC development from CD14 ϩ human monocytes (18). SOCS1 was shown to be involved in this process, as SOCS1 was highly upregulated by TLR signals, thereby suppressing GM-CSF signals.…”
Section: Discussionmentioning
confidence: 99%
“…SOCS1, a member of the SOCS and cytokine-induced Src homology 2 (SH2) protein (CIS) family of intracellular proteins, has emerged as a critical inhibitory molecule for controlling the cytokine response and antigen presentation by DCs, thereby regulating the magnitude of adaptive immunity (14)(15)(16)(17)(18)(19). It has been reported that DCs from SOCS1 knockout mice (SOCS1 Ϫ/Ϫ DCs) were hypersensitive to lipopolysaccharide (LPS) stimulation and exhibited a more mature phenotype than DCs from their wildtype littermates (14).…”
mentioning
confidence: 99%